1991
DOI: 10.3109/01612849109040509
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Headache Patients′ Marital and Family Adjustment

Abstract: The purpose of this study was to compare the marital and family adjustment of headache patients and their spouses, before pain control treatment, to couples without chronic pain. Minuchin's (1978) family systems theory of psychosomatic illness was tested, using an adult sample. This sample consisted of 117 headache-patient-and-spouse couples and a control group of 108 married couples without chronic pain. A survey design was used with marital and family assessment instruments. Marital and family questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Another study using FACES III to investigate family functioning in a group of headache patients reported very different findings from the previous study (Basolo-Kunzer et al, 1991). The authors compared family functioning of 117 headache patients with a control group of 118 normal couples without pain.…”
Section: Literature Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…Another study using FACES III to investigate family functioning in a group of headache patients reported very different findings from the previous study (Basolo-Kunzer et al, 1991). The authors compared family functioning of 117 headache patients with a control group of 118 normal couples without pain.…”
Section: Literature Reviewmentioning
confidence: 81%
“…On the expressiveness subscale of FES, the chronic pain group was significantly more compromised than the normal controls in expressing emotions. To complicate the picture even further, two studies that compared the family functioning of chronic pain patients with normal controls failed to find any significant differences between the two groups (Basolo-Kunzer et al, 1991;Nicassio and Radojevic, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…The chronic pain and family literature provides evidence that supports this perspective (Basolo- Kunzer et al, 1991;Nicassio and Radojevic, 1993). The chronic pain and family literature provides evidence that supports this perspective (Basolo- Kunzer et al, 1991;Nicassio and Radojevic, 1993).…”
Section: Mrs Abrams and The Familymentioning
confidence: 91%
“…We now examine in some depth two studies that failed to show any family dysfunction in chronic pain families (Basolo- Kunzer et al, 1991;Nicassio and Radojvic, 1993). Basolo-Kunzer and associates compared family functioning in a group of 117 headache patients and their spouses with a control group of 108 married couples without pain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is some evidence that suggests that SCCPP experience increased psychological distress, relationship dissatisfaction, financial problems, role changes, and sexual dysfunction (Kerns & Turk, 1984;Leonard & Cano, 2006;Rosenbaum, 2009). However, other research has shown that SCCPP do not necessarily experience distress or negative effects as a result of caregiving (Basolo-Kunzer, Diamond, & Reed, 1991;Feinauer & Steele, 1992;Flor, Breitenstein, & Birbaumer, 1995;Liew et al, 2010). Literature in the areas of positive psychology, resiliency, adjustment, and psychological interventions provide plausible explanations to the varying adjustment ability of caregivers, including stress appraisal, coping resources, personal attributes, and dispositional tendencies (e.g., internal locus of control, optimism, self-efficacy; Carver, Scheier, & Segerstrom, 2010;Horton & Wallander, 2001;Seligman & Csikszentmihalyi, 2000).…”
Section: Chronic Painmentioning
confidence: 99%